Skill shortages and industry clusters: Empirical evidence from German establishment data - Tobias König; Thomas Brenner (Philipps-University Marburg, Department of Geography, 2022)
Regional and sector-specific skill shortages are either foreseeable or a reality in Germany. It is unclear whether shortages of skilled workers are more apparent in industry-specific agglomerations due to competitive labor poaching or less apparent benefitting labor pooling. This paper analyses the association of skill shortages and the level of industrial clustering in Germany. The results show, that firms located in an industrial cluster have a significantly lower chance of experiencing skill shortages in terms of vacancies for qualified jobs. At the same time, if firms located in industrial clusters face skill shortage, they struggle more to fill such vacancies.
Keywords: J23; J63; R10; 330; Skill shortage; cluster; location quotient; Establishment panel data